Role of Human Papillomavirus in Various Cancers: Epidemiology, Screening and Prevention - Ahmed, Waqas; Zaib, Sumera; Ullah, Sami; Fatima, Areej; Zaib, Zainab; Haseeb Azam, Muhammad Abdul; Umar, Usama; Tariq, Muhammad Umair; Aslam, Rabia; Khan, Imtiaz (Mini Reviews in Medicinal Chemistry, 2023)
It is estimated that viral infections contribute 15-20% of all human cancers. Several types of human papillomaviruse (HPV) are related to the development of many cancer types and their treatment. About 200 HPV viruses have been identified, and each type of virus is integrated with a certain type of clinical lesions affecting the areas of skin and mucous membranes. Infections associated with HPV are known to cause multiple cancer types such as uterine cancer, cervical, vaginal carcinoma, and other varieties of carcinomas such as genital and oropharyngeal, penile, and short-lived carcinomas. Most of the HPV types are considered as high-risk mutants that can provoke cervical cancer in females in addition to significant contribution to other cancer types such as anogenital cancer and tumor in head and neck regions. Among them, high risk human papilloma viruses (HR-HPV) subtypes 16 and 18 play a major role in the etiology of cervical cancer worldwide. Although, cervical cancer incidence and fatality rates vary greatly depending on geographical area, it is the leading cause of mortality in women around the world. In addition, it is epidemiologically similar to a sexually transmitted disease of low infectivity. In this review article, the association of HPV with different types of cancers have been explained, but the main focus remains on cervical cancer.
Keywords: epidemiology